1979
DOI: 10.2508/chikusan.50.320
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Water Restriction on Physiological Responses in Fattening Beef Cattle

Abstract: To determine the relation between water restriction and various physiological responses in a hot and cold environment, an investigation was carried out both in summer and in winter.The results are as follows. The water requirement of cattle is determined principally by the physical form and quantity of the ration consumed and the amount of water evaporated from the body surface for cooling. On dairy cattle in a hot environment, OKAMOTO et al.1) suggested that water consumption was related to thermoregulation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2008
2008
2010
2010

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 3 publications
2
2
0
Order By: Relevance
“…Goats subjected to 67% water restriction level ate 402.8 gDM (60.6 gDM/W kg 0.75 ) as against 445.8 gDM (67.0 gDM/W kg 0.75 ) in 33% and 446.0 gDM (67.6 gDM/W kg 0.75 ) in goats that received water ad libitum. The reduction in dry matter intake observed in the present study agrees with Atta (1977), Togashi and Tanaka (1979), Lautier et al (1988), Aganga et al (1989), Ikhatua et al (1992), and Abdelatif and Ahmed (1994) that reported decreased feed intake in various ruminant species when water availability is limited. Gordon (1965) reported that feed intake of sheep declined noticeably by the second day without water.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Goats subjected to 67% water restriction level ate 402.8 gDM (60.6 gDM/W kg 0.75 ) as against 445.8 gDM (67.0 gDM/W kg 0.75 ) in 33% and 446.0 gDM (67.6 gDM/W kg 0.75 ) in goats that received water ad libitum. The reduction in dry matter intake observed in the present study agrees with Atta (1977), Togashi and Tanaka (1979), Lautier et al (1988), Aganga et al (1989), Ikhatua et al (1992), and Abdelatif and Ahmed (1994) that reported decreased feed intake in various ruminant species when water availability is limited. Gordon (1965) reported that feed intake of sheep declined noticeably by the second day without water.…”
Section: Discussionsupporting
confidence: 92%
“…Sheep deprived of water for more than 48 h were found to grow lean and felt dizzy (Umunna et al, 1981). Loss of weight was reported in Yankasa sheep (Aganga et al, 1989), fattening beef cattle (Togashi and Tanaka, 1979), dairy cows (Burgos et al, 2001) deprived water for varying lengths of time.…”
Section: Resumen Doce Cabras No Preñadas (West Africanmentioning
confidence: 99%
“…Goats subjected to 67% water restriction level ate 402.8 gDM (60.6 gDM/W kg 0.75 ) as against 445.8 gDM (67.0 gDM/W kg 0.75 ) in 33% and 446.0 gDM (67.6 gDM/W kg 0.75 ) in goats that received water ad libitum. The reduction in dry matter intake observed in the present study agrees with Atta (1977), Togashi and Tanaka (1979), Lautier et al (1988), Aganga et al (1989), Ikhatua et al (1992), and Abdelatif and Ahmed (1994) that reported decreased feed intake in various ruminant species when water availability is limited. Gordon (1965) reported that feed intake of sheep declined noticeably by the second day without water.…”
Section: Discussionsupporting
confidence: 92%
“…Sheep deprived of water for more than 48 h were found to grow lean and felt dizzy (Umunna et al, 1981). Loss of weight was reported in Yankasa sheep (Aganga et al, 1989), fattening beef cattle (Togashi and Tanaka, 1979), dairy cows (Burgos et al, 2001) deprived water for varying lengths of time.…”
Section: Resumen Doce Cabras No Preñadas (West Africanmentioning
confidence: 99%